Eunuchs and Sacred Boundaries in Islamic Society. - Marmon, Shaun (Oxford University Press, 1995)
In this thought-provoking interdisciplinary work, Shaun Marmon describes how eunuchs, as a category of people who embodied ambiguity, both defined and mediated critical thresholds of moral and physical space in the household, in the palace and in the tomb of pre-modern Islamic society. Theauthor's central focus is on the sacred society of eunuchs who guarded the tomb of the Prophet Muhammad in Medina for over six centuries and whose last representatives still perform many of their time honored rituals to this day. Through Marmon's account, the ""sacred"" eunuchs of Medina becomehistorical guid.